The Impact Of CEO Gender, CEO Characteristic, and Accounting Background on Environmental, Social, and Governance (ESG) - Suhari, Salamatul Insan; Wahyuningtyas , Endah Tri (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study aims to analyze the influence of CEO gender, CEO characteristics, and CEO accounting background on the Environmental, Social, and Governance (ESG) performance of companies listed in the ESG Leaders Index for the period 2019-2023. Using a quantitative approach and secondary data, this research examines how CEO gender, tenure, age, education, and accounting background affect the company's ESG performance. The study results show that female CEOs significantly contribute positively to the improvement of ESG performance, driven by leadership styles and psychological characteristics that support social responsibility and sustainability. CEO characteristics such as tenure and age do not affect ESG performance, while the CEO's education and accounting background positively influence better ESG management and reporting. These findings provide evidence that selecting CEOs with the right profiles is key to promoting the company's ESG performance and also offer practical implications for developing sustainability strategies and corporate governance